Weberowski „model” badań historycznych - Drozdowicz, Zbigniew (Polska Akademia Nauk - "Nauka", 2009)
This paper is a voice in the discussion on research procedures, postulated and put into practice by Max Weber. I’m particularly interested in his historical research and the outcomes he gained from it. I see in it some original solutions, including those, which might successfully be put (and they are) many times in modern humanistic research. Some of them, for example weberian modeling (today called “idealization”), became serious theories. By Weber himself this “modeling” is linked more to a research practice of his, then a formulated theory of scientific research. That’s why I use the quotation marks in the title of my paper.
Keywords: spirit of capitalism; protestant ethics; historical generalizations; modeling; rationality; profession as a mission